2012
DOI: 10.1371/journal.ppat.1002993
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Phosphoproteome of Influenza A and B Viruses by Mass Spectrometry

Abstract: Protein phosphorylation is a common post-translational modification in eukaryotic cells and has a wide range of functional effects. Here, we used mass spectrometry to search for phosphorylated residues in all the proteins of influenza A and B viruses – to the best of our knowledge, the first time such a comprehensive approach has been applied to a virus. We identified 36 novel phosphorylation sites, as well as confirming 3 previously-identified sites. N-terminal processing and ubiquitination of viral proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
160
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(175 citation statements)
references
References 137 publications
(184 reference statements)
14
160
1
Order By: Relevance
“…Mapping of the phosphoproteome of influenza A and B viruses identified multiple phosphorylation sites within NP (12). Three sites, S165, S457, and S402/403, were present within the homooligomerization domain of NP, and it was hypothesized that phosphorylation at these sites might prevent NP oligomerization by inhibiting the interaction between the tail-loop and groove of neighboring NP monomers.…”
mentioning
confidence: 99%
“…Mapping of the phosphoproteome of influenza A and B viruses identified multiple phosphorylation sites within NP (12). Three sites, S165, S457, and S402/403, were present within the homooligomerization domain of NP, and it was hypothesized that phosphorylation at these sites might prevent NP oligomerization by inhibiting the interaction between the tail-loop and groove of neighboring NP monomers.…”
mentioning
confidence: 99%
“…For instance, a mass spectrometry study of the phosphoproteome of influenza A and B viruses revealed that almost all viral proteins, namely, PB2, PB1, PA, HA, NA, NP, M1, M2, NS1, and NEP, are phosphorylated (6). In addition, NP undergoes ubiquitination and deubiquitination, which may play an important role in regulating viral transcription and replication (7).…”
mentioning
confidence: 99%
“…It should also be noted that the peptide of 101 to 105 aa in BM1 satisfied the pattern of a monopartite NLS but was found to lack nuclear import activity. Among the five phosphorylation sites identified in BM1 in the present study, 236S and 237S were reported in a previous study (28), but the roles of the phosphorylation of the these residues in virus life cycle were not investigated. M1 and BM1 were both phosphorylated proteins (29).…”
Section: Discussionmentioning
confidence: 56%